Morphologic abnormalities in Amblyomma mixtum, Amblyomma naponense, Amblyomma cf. oblongoguttatum and Amblyomma tapirellum (Acari: Ixodidae) of Costa Rica. - Domínguez, Lillian G. (2021)
In this work, we describe abnormalities in adults of Amblyomma mixtum, Amblyomma naponense, Amblyomma cf. oblongoguttatum and Amblyomma tapirellum of Costa Rica. General anomalies manifested as body asymmetry, nanism, and gigantism, while local anomalies occurred in the legs, festoons, anal pore and spiracle. These are the firsts mention of abnormalities in ticks from Costa Rica.